Biography of Grandma Prisbrey - Paul, Daniel
Tressa "Grandma" Prisbrey (birthname- Thresie Luella Shafer) was born January 19, 1896 in Easton, Minnesota. Her formal education consisted of attending public school until 1908, when her family moved to a homestead outside Minot, North Dakota.